Antioxidant Pathways in Alzheimer's Disease: Possibilities of Intervention - Vina, J.; LLoret, A.; Giraldo, E.; C. Badia, M.; D. Alonso, M. (Current Pharmaceutical Design, 2011)
Alzheimer's disease (AD) is closely related to the occurrence of oxidative stress. It was claimed that all pathophysiological mechanisms involved in the onset and progression of AD are related to oxidative stress. Thus, it is important to evaluate if there is oxidative stress as well as the mechanism by which this happens in AD patients as well as in animal models of AD. Extracellular plaques of amyloid b peptides (Aβ), a hallmark of the disease, have been postulated to be more protective than damaging in terms of oxidative stress because they may be chemical sinks in which heavy metals are placed. More than a decade ago we reasoned that damage due to Ab might be caused not by extracellular, but rather intracellular Ab peptide interacting with normal cell metabolism. Ab binds to mitochondrial membranes, interacts with heme and thus interferes with the normal electron flow through the respiratory chain. This results in a faulty mitochondrial energy metabolism and in an increased production of reactive oxygen species (ROS). The low mitochondrial energy metabolism may important to explain the hypo metabolism observed in AD patients in vivo (measured by positron emission tomography) and in isolated neurons incubated in the presence of Ab peptide. The increased ROS production results in oxidative stress. The occurrence of such stress provides the basis for a putative treatment of AD with antioxidants. Major efforts have been made to determine whether antioxidant supplementation could be a means of preventing, or even treating AD, but this idea is far from being well- established. We found that even though there is oxidative stress in AD, the administration of antioxidant vitamins, particularly vitamin E, is not effective in preventing the progression of the disease in all patients. We termed this the vitamin E paradox in AD. The paradox is the fact that for some patients, vitamin E could even be detrimental whereas for others vitamin E treatment partially prevents the loss memory associated with the progression of the disease. It is clear, however, that increasing the intake of fruits and vegetables rich in antioxidant vitamins, prevents or retards the onset of AD. Thus, the issue of whether antioxidant treatment is of use in AD is not settled and more research is warranted to clarify this point.
Keywords: oestrogens